2015
DOI: 10.1017/s1751731115000683
|View full text |Cite
|
Sign up to set email alerts
|

The ability of genetically lean or fat slow-growing chickens to synthesize and store lipids is not altered by the dietary energy source

Abstract: The increasing use of unconventional feedstuffs in chicken's diets results in the substitution of starch by lipids as the main dietary energy source. To evaluate the responses of genetically fat or lean chickens to these diets, males of two experimental lines divergently selected for abdominal fat content were fed isocaloric, isonitrogenous diets with either high lipid (80 g/kg), high fiber (64 g/kg) contents (HL), or low lipid (20 g/kg), low fiber (21 g/kg) contents (LL) from 22 to 63 days of age. The diet ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…However, the results of the present study are in agreement with previous observations that indicated a mixture of BCAA that did not affect body weight gain, feed intake or feed efficiency in fast-growing broilers (Bhanja and Mandal, 2005). The lack of effects of BCAA blend used in the present study can firstly be explained by the fact that the fastgrowing birds were better able to perform with commercial basal diet due to the fact that nutrient requirements increase depending on growth rate (Sarica et al, 2009;Yamak et al, 2014), and also they may be better able to digest the basal diet due to the development of the digestive tract and organs (Sarica et al, 2009;Baéza et al, 2015). In fact, the effect of BCAA bland was not significant on the dressing percentage, the relative weights of the whole GIT, pancreas and edible inner organs, including gizzard at slaughter age (data not shown).…”
Section: Resultsmentioning
confidence: 77%
“…However, the results of the present study are in agreement with previous observations that indicated a mixture of BCAA that did not affect body weight gain, feed intake or feed efficiency in fast-growing broilers (Bhanja and Mandal, 2005). The lack of effects of BCAA blend used in the present study can firstly be explained by the fact that the fastgrowing birds were better able to perform with commercial basal diet due to the fact that nutrient requirements increase depending on growth rate (Sarica et al, 2009;Yamak et al, 2014), and also they may be better able to digest the basal diet due to the development of the digestive tract and organs (Sarica et al, 2009;Baéza et al, 2015). In fact, the effect of BCAA bland was not significant on the dressing percentage, the relative weights of the whole GIT, pancreas and edible inner organs, including gizzard at slaughter age (data not shown).…”
Section: Resultsmentioning
confidence: 77%
“…However, the percentage of polyunsaturated fatty acids was lower for the LF diet than for the HF diet. The enzymatic activity of FAS was significantly affected by diet treatments in the lean or fat chickens, and was lower in the HF diet ( Baeza et al, 2015 ). By contrast, chickens fed a high-fat diet and low protein showed higher abdominal fat deposition than chickens fed a low-fat and high-protein diet, and this difference was more remarkable for fat chickens ( Swennen et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The amounts of saturated, mono-unsaturated and poly-unsaturated fatty acids were similar in the two diets. Detailed compositions of LF and HF diets are precisely described in our previous study [ 3 ] and are summarized in the Additional file 1 .…”
Section: Methodsmentioning
confidence: 99%
“…We finally used these elementary variables to compute the relative percentages in SFA (saturated FA), MFA (mono-unsaturated FA) and PUFA (poly-unsaturated FA), n-6 and n-3 FA families, as well as the n-6/n-3 ratio. For additional information about methods and measures, see [ 3 , 10 ]. A Student t test was performed using the t.test function in R for testing the dietary effect in each of the three FA classes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation